Alumina ceramic granulation powder, preparation method thereof and high-density alumina ceramic
The alumina slurry is prepared by ball milling and stirring, and an appropriate amount of additives is added during the spray granulation process, which solves the problems of uneven density and poor processing performance of alumina ceramic granulation powder, and achieves high-density and good processing performance of alumina ceramic granulation powder.
Patent Information
- Application Number
- CN202411992928.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-18
AI Technical Summary
The existing alumina ceramic granulated powder has uneven density after sintering, and its processing performance and yield are not high, which cannot meet the production requirements of alumina ceramics for semiconductor equipment.
By weighing raw materials according to the determined solid content, alumina slurry is prepared by ball milling and stirring, and additives of different proportions are added in stages during the stirring process, and the slurry is spray granulated and sieved to obtain alumina ceramic granulation powder with high loose density and good fluidity.
The high loose density and fluidity of alumina ceramic granulated powder are achieved, and the density of alumina ceramics after sintered is improved, which meets the production requirements of alumina ceramics for semiconductor equipment.
Smart Images

Figure CN119638383A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of alumina spray granulation, and in particular relates to an alumina ceramic granulation powder and a preparation method thereof, and a high-density alumina ceramic. Background Art
[0002] Spray granulation is a method for producing high-quality ceramic granulation powder. It can be used in industry to prepare special ceramics such as zirconia ceramics, silicon nitride ceramics, and alumina ceramics. In the production process of alumina ceramics, the powder particles obtained by spray granulation have the advantages of regular, spherical shape, good particle size distribution and normal distribution, and good forming and sintering characteristics.
[0003] Spray granulation usually affects the compactness and processing performance of alumina ceramics by affecting the bulk density and fluidity of the granulated powder, thereby affecting the density of the ceramic after sintering. In order to make the granulated powder reach the fluidity required for production and processing, a binder is usually added before granulation. Polyvinyl alcohol (PVA) is widely used in industry as a relatively economical binder. During the spray granulation process, the addition of PVA will form a very thin lubricating film on the surface of the particles, which improves the surface roughness and reduces the sliding resistance between particles, thereby improving the fluidity of the granulated powder. However, excessive addition of PVA will also cause the surface of the particles to form a hard shell, which cannot be fully broken during the molding process, and the edges of the green body will collapse and crack during processing. At the same time, pores will appear in the ceramic cavity after sintering, and the density of the ceramic after sintering will be uneven. In addition, the alcoholysis degree and addition method of PVA also affect the quality and performance of the granulated powder to a certain extent.
[0004] Therefore, in order to make the granulated powder have better fluidity and greater loose density, improve the processing performance and yield of its green products, ensure that the sintered porcelain body has good density, and meet the requirements of semiconductor equipment parts production, it is necessary to optimize the material production formula and process, and timely adjust the ratio, addition time and addition form of additives such as binders in spray granulation.
[0005] If the formula in patent CN114751728A is used, the density of the obtained granulated powder after sintering reaches 3.94g / cm 3 , but the bulk density of the powder is only 1.01~1.05g / cm 3The purity is about 99.1%, which does not meet the semiconductor industry's requirement that the purity of aluminum oxide sheets should be greater than 99.5%. Patent CN104150883A uses a composite additive to modify the surface of the spray granulation powder particles, so that the granulation powder has the granular shape of wet spray granulation, and can achieve a fineness similar to dry grinding granulation powder (micro powder) during use. The fired alumina ceramic products have high precision, no deformation, and good polishing effect, but the density of the ceramic body after sintering is only 3.60-3.73g / cm 3 .
[0006] Therefore, in view of the above problems, it is necessary to further optimize the preparation process of alumina ceramic granulated powder so that the prepared alumina ceramic granulated powder has good fluidity and high loose density, and ensure that the porcelain body obtained by sintering the alumina ceramic granulated powder has a high density. Summary of the invention
[0007] In order to solve the above-mentioned technical problems, the present application provides an alumina ceramic granulated powder, a preparation method thereof and a high-density alumina ceramic. The prepared alumina ceramic granulated powder has a high loose density, good fluidity, and excellent molding and processing properties. The alumina ceramic sintered from the alumina ceramic granulated powder has a high density and meets the production requirements of alumina ceramics for semiconductor equipment.
[0008] The first object of the present application is to provide a method for preparing alumina ceramic granulated powder.
[0009] The above application purpose 1 is achieved through the following technical solutions:
[0010] A method for preparing alumina ceramic granulated powder comprises the following steps:
[0011] S1, weighing the required raw materials according to mass percentage for use, wherein the alumina raw powder accounts for 75% and the balance is pure water;
[0012] S2, put alumina grinding balls into the ball mill, and put the weighed alumina raw powder and pure water into the ball mill in the order of water first and powder later for ball milling. The ball milling time is 3 hours and the speed of the ball mill is 35 Hz;
[0013] S3, sieving the mixture of grinding balls and slurry in the ball mill jar through a screen to separate the grinding balls and slurry;
[0014] S4, pouring the slurry obtained after screening into a stirring tank for stirring, adding a dispersant, a binder, a plasticizer, and a lubricant in stages during the stirring process, and adjusting the pH value of the slurry to obtain an alumina slurry;
[0015] S5, using a spray granulator to spray granulate the alumina slurry to obtain alumina ceramic granulated powder.
[0016] Preferably, the method for preparing the alumina ceramic granulated powder further comprises the following steps:
[0017] S6, using a double-layer screen to sieve the alumina ceramic granulated powder obtained by spray granulation to obtain alumina ceramic granulated powder with a particle size of 30 μm to 100 μm.
[0018] Preferably, in step S4, the dispersant, binder, plasticizer, and lubricant are added in stages during the stirring process, and the pH value of the slurry is adjusted to obtain the alumina slurry, which includes:
[0019] First add dispersant and binder, then stir for 1 hour, then add plasticizer, then stir for 0.5 hour, then add lubricant, then stir for 0.5 hour, then adjust the pH value of the slurry to the target value, then stir for 0.5 hour to obtain alumina slurry.
[0020] Preferably, in step S4, after adding the dispersant and the binder, if foam appears in the slurry during stirring, a proper amount of defoaming agent is added until no bubbles are visible on the surface of the slurry.
[0021] Preferably, in step S4, the dispersant is added in a proportion of 0.5% to 5% of the mass of the alumina raw powder, the binder is added in a proportion of 1% to 20% of the mass of the alumina raw powder, the plasticizer is added in a proportion of 1% to 20% of the mass of the alumina raw powder, and the lubricant is added in a proportion of 1% to 5% of the mass of the alumina raw powder.
[0022] Preferably, in step S2, the alumina grinding balls are selected to have a purity of 99.9%, and the mass of the alumina grinding balls: the mass of the alumina raw powder = 2:1.
[0023] Preferably, in step S5, the inlet temperature of the spray granulator is below 200° C., the outlet temperature is below 150° C., and the rotation speed of the atomizing disk is below 50 Hz.
[0024] Preferably, the dispersant is selected from one of PVC resin, polyethylene wax, ammonium carboxylate, acrylic resin and ammonium acrylic acid salt; the binder is selected from polyvinyl alcohol solution; the plasticizer is selected from one or more of polyethylene glycol, glycerol and polyvinyl chloride; the lubricant is selected from one of aqueous paraffin, glycerol and stearic acid emulsion.
[0025] The second object of the present application is to provide an alumina ceramic granulated powder.
[0026] The second purpose of the above application is achieved through the following technical solutions:
[0027] An alumina ceramic granulated powder is prepared by using the method for preparing the alumina ceramic granulated powder as described in any one of the above application purposes.
[0028] The third object of this application is to provide a high-density alumina ceramic.
[0029] The third application purpose is achieved through the following technical solutions:
[0030] A high-density alumina ceramic is obtained by cold isostatic pressing and sintering the alumina ceramic granulated powder as described in the second application object.
[0031] The above technical solution of the present application has the following advantages compared with the prior art:
[0032] The present application weighs the raw materials according to the determined solid content, prepares the alumina slurry by ball milling and stirring, and adds different types of additives in different proportions in stages during the stirring process, so that each additive is fully and evenly distributed in the slurry, and finally the slurry is spray granulated and sieved. The process method is simple to operate, easy to promote and produce, and the alumina ceramic granulated powder prepared by this method has a high loose density, good fluidity, and excellent molding and processing performance. The alumina ceramic sintered by the granulated powder has a high density and meets the production requirements of alumina ceramics for semiconductor equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0034] Figure 1 This is a schematic diagram of a process for preparing an alumina ceramic granulated powder in one embodiment of the present application;
[0035] Figure 2 This is an electron microscope image of the alumina ceramic granulated powder in Example 2 of the present application;
[0036] Figure 3 This is an electron microscope image of the alumina ceramic granulated powder in Example 6 of the present application;
[0037] Figure 4 This is an electron microscope image of the alumina ceramic green body prepared from the alumina ceramic granulated powder in Example 2 of the present application;
[0038] Figure 5 This is an electron microscope image of the alumina ceramic green body prepared from the alumina ceramic granulated powder in Example 6 of the present application. DETAILED DESCRIPTION
[0039] In order to enable those skilled in the art to better understand the technical solutions in this application, the technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0040] In the embodiments provided in the present application, it should be understood that the disclosed methods and systems can be implemented in other ways. The system embodiments described below are merely schematic. For example, the division of units and modules is only a logical function division. There may be other division methods in actual implementation, such as: multiple units or modules can be combined, or can be integrated into another system, or some features can be ignored, or not executed. In addition, the coupling, direct coupling, or communication connection between the components shown or discussed can be through some interfaces, indirect coupling or communication connection of devices or modules, which can be electrical, mechanical or other forms.
[0041] In addition, all functional units in the embodiments of the present application may be integrated into one processor, or each unit may be a separate device, or two or more units may be integrated into one device; each functional unit in the embodiments of the present application may be implemented in the form of hardware or in the form of hardware plus software functional units.
[0042] A person skilled in the art can understand that all or part of the steps of the following method embodiments can be completed by program instructions and related hardware. The aforementioned program instructions can be stored in a computer-readable storage medium. When the program instructions are executed, the steps of the following method embodiments are executed; and the aforementioned storage medium includes: a mobile storage device, a read-only memory (ROM), a magnetic disk or an optical disk, and other media that can store program codes.
[0043] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of this application, "multiple" and "several" mean two or more, unless otherwise clearly and specifically defined.
[0044] like Figure 1 As shown, the embodiment of the present application provides a method for preparing alumina ceramic granulated powder, which may include the following steps:
[0045] S1, weighing the required raw materials according to mass percentage for use, wherein the alumina raw powder accounts for 75% and the balance is pure water;
[0046] S2, put alumina grinding balls into the ball mill, and put the weighed alumina raw powder and pure water into the ball mill in the order of water first and powder later for ball milling. The ball milling time is 3 hours and the speed of the ball mill is 35 Hz;
[0047] S3, sieving the mixture of grinding balls and slurry in the ball mill jar through a screen to separate the grinding balls and slurry;
[0048] S4, pouring the slurry obtained after screening into a stirring tank for stirring, adding a dispersant, a binder, a plasticizer, and a lubricant in stages during the stirring process, and adjusting the pH value of the slurry to obtain an alumina slurry;
[0049] S5, using a spray granulator to spray granulate the alumina slurry to obtain alumina ceramic granulated powder.
[0050] The preparation method of the alumina ceramic granulation powder of this embodiment is as follows: first, the required raw materials are weighed according to the mass percentage for use, with the alumina raw powder accounting for 75% and the remainder being pure water; then, alumina grinding balls are placed in a ball mill, and the weighed alumina raw powder and pure water are placed in the ball mill in the order of water first and powder later for ball milling, the ball milling time is 3 hours, and the speed of the ball mill is 35Hz; then, the mixture of the grinding balls and the slurry in the ball mill is sieved with a sieve to separate the grinding balls and the slurry; the slurry obtained after sieving is poured into a stirring kettle for stirring, and during the stirring process, a dispersant, a binder, a plasticizer, and a lubricant are added in stages in turn, and the pH value of the slurry is adjusted to obtain an alumina slurry; finally, a spray granulator is used to spray granulate the alumina slurry to obtain an alumina ceramic granulation powder.
[0051] In this embodiment, the raw materials are weighed according to the determined solid content, and the alumina slurry is prepared by ball milling and stirring. During the stirring process, different types of additives with different proportions are added in stages in sequence, so that each additive is fully and evenly distributed in the slurry, and finally the slurry is spray granulated. The process method is simple to operate, easy to promote and produce, and the alumina ceramic granulated powder prepared by the method has a high bulk density, good fluidity, and excellent molding and processing performance. The alumina ceramic sintered by the granulated powder has a high density and meets the production requirements of alumina ceramics for semiconductor equipment.
[0052] In one embodiment, the method for preparing alumina ceramic granulated powder further comprises the following steps:
[0053] S6, using a double-layer screen to sieve the alumina ceramic granulated powder obtained by spray granulation to obtain alumina ceramic granulated powder with a particle size of 30 μm to 100 μm.
[0054] In one embodiment, in step S4, the dispersant, the binder, the plasticizer, and the lubricant are added in stages during the stirring process, and the pH value of the slurry is adjusted to obtain the alumina slurry, which includes:
[0055] First, a dispersant and a binder are added, and then stirred for 1 hour, then a plasticizer is added, and then stirred for 0.5 hours, then a lubricant is added, and then stirred for 0.5 hours, and then the pH value of the slurry is adjusted to a target value, and then stirred for 0.5 hours to obtain an alumina slurry. Specifically, in this embodiment, when adjusting the pH value of the slurry, the pH value of the slurry is adjusted to 8-9 by adding oxalic acid.
[0056] In one embodiment, in step S4, after adding the dispersant and the binder, if foam appears in the slurry during the stirring process, add an appropriate amount of defoamer until no bubbles are visible on the surface of the slurry. Specifically, the defoamer can be selected from butyl phosphate and the like. Specifically, in this embodiment, when adding the defoamer, add it slowly drop by drop using a rubber-tipped dropper until no foam is observed by the naked eye and then stop adding.
[0057] In one embodiment, in step S4, the dispersant is added in a ratio of 0.5% to 5% of the mass of the alumina raw powder, the binder is added in a ratio of 1% to 20% of the mass of the alumina raw powder, the plasticizer is added in a ratio of 1% to 20% of the mass of the alumina raw powder, and the lubricant is added in a ratio of 1% to 5% of the mass of the alumina raw powder.
[0058] In one embodiment, in step S2, the alumina grinding balls are selected to have a purity of 99.9%, and the mass of the alumina grinding balls: the mass of the alumina raw powder = 2:1.
[0059] In one embodiment, in step S5, the inlet temperature of the spray granulator is below 200° C., the outlet temperature is below 150° C., and the atomizing disk rotation speed is below 50 Hz.
[0060] In one embodiment, the dispersant is selected from one of PVC resin, polyethylene wax, ammonium carboxylate, acrylic resin and ammonium acrylic acid salt; the binder is selected from polyvinyl alcohol solution; the plasticizer is selected from one or more of polyethylene glycol, glycerol and polyvinyl chloride; the lubricant is selected from one of aqueous paraffin, glycerol and stearic acid emulsion.
[0061] The embodiment of the present application also provides an alumina ceramic granulated powder, which is prepared by the preparation method of the alumina ceramic granulated powder described in any of the above embodiments.
[0062] The embodiment of the present application also provides a high-density alumina ceramic, which is obtained by cold isostatic pressing and then sintering the alumina ceramic granulated powder described in the above embodiment.
[0063] Specifically, in this embodiment, the pressure of cold isostatic pressing is 130 MPa, and the holding time is 300 s.
[0064] In order to better understand the advantages of the method for preparing alumina ceramic granulated powder according to the embodiment of the present application, the process flow and technical effects thereof are demonstrated and explained with multiple embodiments and a comparative example below.
[0065] In actual production, the dispersant addition ratio is any ratio between 0.5% and 5% of the mass of the alumina raw powder. The dispersant can be any one of PVC resin, polyethylene wax, carboxylic acid ammonium salt, acrylic resin and acrylic acid ammonium salt. In the following embodiments, the dispersant is preferably domestic PVC resin, and the addition ratio is preferably 0.7% of the mass of the alumina raw powder.
[0066] The binder addition ratio is any ratio between 1% and 20% of the mass of the alumina raw powder. The binder can be a polyvinyl alcohol solution or other binders. In the following embodiments, the binder is preferably a polyvinyl alcohol solution, and the addition ratio is preferably 5% of the mass of the alumina raw powder.
[0067] The plasticizer addition ratio is any ratio of 1% to 20% of the mass of the alumina raw powder. The plasticizer can be selected from one or more of polyethylene glycol, glycerol and polyvinyl chloride. In the following embodiments, the plasticizer is selected from one of polyethylene glycol, glycerol and polyvinyl chloride, and the addition ratio is one of 1%, 3% and 20%.
[0068] The lubricant addition ratio can be any ratio between 1% and 5% of the mass of the alumina raw powder. The lubricant can be any one of aqueous paraffin, propylene glycol and stearic acid emulsion. In the following embodiments, the lubricant is preferably stearic acid emulsion, and the addition ratio is preferably 1.8% of the mass of the alumina raw powder.
[0069] Embodiment 1:
[0070] The specific process is as follows:
[0071] Step 1. Weigh alumina powder and pure water according to the ratio of slurry solid content of 75%. In this embodiment, weigh 20 kg of alumina powder and 6.67 kg of pure water. Put the weighed alumina powder and water into the ball mill in the order of water first and powder later for ball milling. The alumina grinding balls in the ball mill are selected with a purity of 99.9%, the mass of the grinding balls added is 40 kg, the ball mill speed is 35 Hz, and the ball milling time is 3 hours.
[0072] Step 2: After ball milling, sieve the grinding balls, pour the mixed slurry into a stirring kettle for stirring, add a dispersant (PVC resin) with a mass fraction of 0.7% of alumina raw powder and a binder (polyvinyl alcohol solution) with a mass fraction of 5% of alumina raw powder during the stirring process, and mix and stir for 1 hour; then add a plasticizer (propylene glycol) with a mass fraction of 1% of alumina raw powder, mix and stir for 0.5 hours, then add a lubricant (stearic acid emulsion) with a mass fraction of 1.8% of alumina raw powder, and mix and stir for 0.5 hours; then add oxalic acid to adjust the pH value of the slurry until the pH value of the slurry is 8-9, and then continue to mix and stir for 0.5 hours.
[0073] Step 3: spray granulate the mixed slurry. The inlet temperature of the spray dryer is 160°C, and the outlet temperature is 100°C. The slurry feeding flow rate is automatically adjusted according to the inlet and outlet temperatures. The atomizing disk speed is 30 Hz.
[0074] Step 4: Screen the powder to obtain an alumina ceramic granulated powder with a particle size of 45 to 60 μm, a loose density of 1.20 g / cm3, and a fluidity of 66 s / 50 g.
[0075] Step 5: Use the alumina ceramic granulation powder to perform cold isostatic pressing and sintering of Pin. The cold isostatic pressing pressure is 130 MPa. The density of the obtained ceramic body after sintering is 3.941 g / cm3.
[0076] Embodiment 2:
[0077] The implementation steps of this embodiment are basically the same as those of embodiment 1, the only difference being that the content of the plasticizer in step 2 is 3% of the mass of the original alumina powder.
[0078] The powder was sieved to obtain an alumina ceramic granulated powder with a particle size of 45 to 60 μm, a loose density of 1.22 g / cm3, and a fluidity of 65 s / 50 g.
[0079] The density of the ceramic body obtained after sintering the alumina ceramic granulated powder is 3.944g / cm3.
[0080] Embodiment 3:
[0081] The implementation steps of this embodiment are basically the same as those of embodiment 1, the only difference being that the content of the plasticizer in step 2 is 20% of the mass of the original alumina powder.
[0082] The powder was sieved to obtain an alumina ceramic granulated powder with a particle size of 45 to 60 μm, a loose density of 1.20 g / cm3, and a fluidity of 68 s / 50 g.
[0083] The density of the ceramic body obtained after sintering the alumina ceramic granulated powder is 3.938g / cm3.
[0084] Embodiment 4:
[0085] The implementation steps of this embodiment are basically the same as those of Example 2, the only difference being that the plasticizer used in step 2 is polyethylene glycol.
[0086] The powder was sieved to obtain an alumina ceramic granulated powder with a particle size of 45 to 60 μm, a loose density of 1.13 g / cm3, and a fluidity of 72 s / 50 g.
[0087] The density of the ceramic body obtained after sintering the alumina ceramic granulated powder is 3.907g / cm3.
[0088] Embodiment 5:
[0089] The implementation steps of this embodiment are basically the same as those of Embodiment 2, the only difference being that the plasticizer used in Step 2 is polyvinyl chloride.
[0090] The powder was sieved to obtain an alumina ceramic granulated powder with a particle size of 45 to 60 μm, a loose density of 1.06 g / cm3, and a fluidity of 75 s / 50 g.
[0091] The density of the ceramic body obtained after sintering the alumina ceramic granulated powder is 3.926g / cm3.
[0092] Embodiment 6:
[0093] The implementation steps of this embodiment are basically the same as those of Embodiment 2, the only difference being that the content of the plasticizer in Step 2 is 0% of the mass of the original alumina powder, that is, no plasticizer is added.
[0094] The powder was sieved to obtain an alumina ceramic granulated powder with a particle size of 45 to 60 μm, a loose density of 1.1.01 g / cm3, and a fluidity of 82 s / 50 g.
[0095] The density of the ceramic body obtained after sintering the alumina ceramic granulated powder is 3.833g / cm3.
[0096] The experimental results comparison table of the above 6 embodiments is as follows:
[0097]
[0098] Among the above 6 embodiments, embodiment 6 is a comparative example, that is, no plasticizer is added during the slurry stirring process in step 2;
[0099] Examples 1 to 5 analyze the advantages of the present application from two aspects: the type and content of the added plasticizer.
[0100] The above-mentioned plasticizer can reduce the crystallinity of the polymer molecular chain, that is, increase the plasticity of the polymer, prevent the binder from making the slurry viscosity too high, reduce the transfer temperature of the alumina ceramic granulation powder, and make the interface of the particles easily destroyed during spray drying, thereby improving the fluidity, bulk density and sinterability of the alumina ceramic granulation powder, and improving the ceramic body density of the alumina ceramic obtained by sintering. In other words, it can improve the flexibility of the binder, promote the plastic deformation of the particles, and thus improve the sinterability.
[0101] By comparing the measurement results of the above 6 embodiments, it can be seen that:
[0102] Compared with Example 6, in Examples 2 to 5, the fluidity and bulk density of the prepared alumina ceramic granulated powder are significantly improved, and the magnet density of the alumina ceramic finished product obtained after sintering is also significantly increased, indicating that the addition of plasticizer during the stirring process can improve the fluidity and bulk density of the alumina ceramic granulated powder, and increase the magnet density of the alumina ceramic finished product obtained after sintering. The specific analysis is as follows:
[0103] 1. Compared with Example 2, different plasticizers were used in Example 4 and Example 5. The results showed that when the mass ratio of the added plasticizer was constant, the fluidity and bulk density of the alumina ceramic granulated powder obtained and the magnet density of the alumina ceramic product obtained after sintering were better than those of other plasticizers when glycerol was used as the plasticizer;
[0104] 2. In Examples 1 to 3, propylene glycol is used as the plasticizer, but the addition ratio of the plasticizer is different. The results show that when the type of plasticizer is the same and the addition amount of the plasticizer is about 3%, the fluidity and loose density of the obtained alumina ceramic granulated powder and the magnet density of the alumina ceramic product obtained after sintering are better than other addition ratios.
[0105] like Figure 2 , Figure 3 As shown, by comparing the granulated powder particles at 200 times ( Figure 2 This is an electron microscope image of the alumina ceramic granulated powder in Example 2; Figure 3 is an electron microscope image of the alumina ceramic granulated powder in Example 6), it can be seen that Figure 3 The granulated powder particles obtained in Example 6 shown in the figure have obvious gourd-shaped and sticky particles, and apple-shaped particles account for more than 50%. The overall sphericity of the particles is poor, and there are obvious concave-convex defects on the surface; Figure 2 The granulated powder particles obtained in Example 2 shown have a significantly reduced proportion of apple-shaped particles, no gourd-shaped particles appear in the powder, and the surface is smoother without obvious defects, and the overall sphericity is better.
[0106] like Figure 4 , Figure 5 As shown, by observing the cross section of the green body after granulation powder molding at 200 times ( Figure 4 This is an electron microscope image of the alumina ceramic green body prepared from the alumina ceramic granulated powder in Example 2;
[0107] Figure 5 : This is an electron microscope image of the alumina ceramic green body prepared from the alumina ceramic granulated powder in Example 6. It can be seen that Figure 5 The green body obtained in Example 6 shown in the figure still has a lot of uncrushed particles after compaction, and the overall structure of the green body is loose, and there are many gaps between the particles, which is not conducive to the density of the porcelain body after sintering; Figure 4 The green body obtained in Example 2 shown has relatively more crushed spherical particles and a denser structure, which is beneficial to the processing in the green body stage and the increase of density after sintering.
[0108] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.
[0109] Professionals may further appreciate that the units and algorithm steps of each example described in conjunction with the embodiments disclosed in this embodiment can be implemented with electronic hardware, computer software, or a combination of the two. In order to clearly illustrate the interchangeability of hardware and software, the composition and steps of each example have been generally described in terms of function in the above description. Whether these functions are performed in hardware or software depends on the specific application and design constraints of the technical solution. Professionals and technicians may use different methods to implement the described functions for each specific application, but such implementation should not be considered to be beyond the scope of this application.
[0110] The steps of the method or algorithm described in the embodiments disclosed in this embodiment can be directly implemented by hardware, software modules executed by a processor, or a combination of the two. The software module can be placed in a random access memory (RAM), a memory, a read-only memory (ROM), an electrically programmable ROM, an electrically erasable programmable ROM, a register, a hard disk, a removable disk, a CD-ROM, or any other form of storage medium known in the technical field.
[0111] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined in the present embodiment may be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown in the present embodiment, but will conform to the widest scope consistent with the principles and novel features disclosed in the present embodiment.
Claims
1. A method for preparing alumina ceramic granulated powder, characterized in that: The steps include: S1, weighing the required raw materials according to mass percentage for use, wherein the alumina raw powder accounts for 75% and the balance is pure water; S2, put alumina grinding balls into the ball mill, and put the weighed alumina raw powder and pure water into the ball mill in the order of water first and powder later for ball milling. The ball milling time is 3 hours and the speed of the ball mill is 35 Hz; S3, sieving the mixture of grinding balls and slurry in the ball mill jar through a screen to separate the grinding balls and slurry; S4, pouring the slurry obtained after screening into a stirring tank for stirring, adding a dispersant, a binder, a plasticizer, and a lubricant in stages during the stirring process, and adjusting the pH value of the slurry to obtain an alumina slurry; S5, using a spray granulator to spray granulate the alumina slurry to obtain alumina ceramic granulated powder.
2. The method for preparing alumina ceramic granulated powder according to claim 1, characterized in that: The following steps are also included: S6, using a double-layer screen to sieve the alumina ceramic granulated powder obtained by spray granulation to obtain alumina ceramic granulated powder with a particle size of 30 μm to 100 μm.
3. The method for preparing alumina ceramic granulated powder according to claim 1, characterized in that: In step S4, the dispersant, binder, plasticizer, and lubricant are added in stages during the stirring process, and the pH value of the slurry is adjusted to obtain an alumina slurry comprising: First add dispersant and binder, then stir for 1 hour, then add plasticizer, then stir for 0.5 hour, then add lubricant, then stir for 0.5 hour, then adjust the pH value of the slurry to the target value, then stir for 0.5 hour to obtain alumina slurry.
4. The method for preparing alumina ceramic granulated powder according to claim 3, characterized in that: In step S4, after adding the dispersant and the binder, if foam appears in the slurry during stirring, add an appropriate amount of defoaming agent until no bubbles are visible on the surface of the slurry.
5. The method for preparing alumina ceramic granulated powder according to claim 3, characterized in that: In step S4, the dispersant is added in a ratio of 0.5% to 5% of the mass of the alumina raw powder, the binder is added in a ratio of 1% to 20% of the mass of the alumina raw powder, the plasticizer is added in a ratio of 1% to 20% of the mass of the alumina raw powder, and the lubricant is added in a ratio of 1% to 5% of the mass of the alumina raw powder.
6. The method for preparing alumina ceramic granulated powder according to claim 1, characterized in that: In step S2, the alumina grinding balls are selected with a purity of 99.9%, and the mass of the alumina grinding balls: the mass of the alumina raw powder = 2:
1.
7. The method for preparing alumina ceramic granulated powder according to claim 1, characterized in that: In step S5, the inlet temperature of the spray granulator is below 200°C, the outlet temperature is below 150°C, and the atomizing disk rotation speed is below 50 Hz.
8. The method for preparing alumina ceramic granulated powder according to any one of claims 1 to 7, characterized in that: The dispersant is selected from one of PVC resin, polyethylene wax, ammonium carboxylate, acrylic resin and ammonium acrylic acid salt; the binder is selected from polyvinyl alcohol solution; the plasticizer is selected from one or more of polyethylene glycol, glycerol and polyvinyl chloride; the lubricant is selected from one of water-based paraffin, glycerol and stearic acid emulsion.
9. An alumina ceramic granulated powder, characterized in that: The alumina ceramic granulated powder is prepared by the preparation method of any one of claims 1 to 8.
10. A high-density alumina ceramic, characterized in that: The alumina ceramic granulated powder as claimed in claim 9 is obtained by cold isostatic pressing and then sintering.
Citation Information
Patent Citations
Preparation method of alumina granulating powder
CN104150883A
Preparation method of aluminum oxide ceramic granulation powder
CN114751728A
High-strength ceramic metallization method
CN118619716A
Alumina sintered body and its producing method
CN1244513A
Production of alumina base plate
JP1993058715A
Cited By
Ultrahigh-density aluminum oxide ceramic material and preparation method thereof
CN120794586A